Guy’s Stone Score: A Predictive Tool for Outcomes of Percutaneous Nephrolithotomy - Sharif, Imran; Khalid, Salman El; Shaikh, Jahanzeb; Muhammad Hammad Mithani; Siddiq Awan, Adnan; Anis Khan, Shariq (International Journal of Endorsing Health Science Research, 2021)
Background: Predicting stone clearance before intervention can be useful to plan the modality of treatment and calculate the cost of procedures. Therefore, this study aims to determine the frequency of successful stone clearance in a patient undergoing percutaneous nephrolithotomy (PCNL) with different categories of Guy's Stone Score (GSS). Methodology: A total of 115 patients undergoing standard PCNL from January to December 2018 were included in this study. According to GSS I-IV, patients were then categorized into four groups after having pre-operative Computed Tomography of Kidney, Ureter, and Bladder (KUB). All the patients received standard general anesthesia and underwent standard PCNL in a prone position. The Percutaneous nephrostomy 18-gauge needle is passed into the pelvis of the kidney, Pelvi-calyceal system opacified and confirmed using fluoroscopy, a guidewire is passed, and 30 Fr Amplatz sheath is introduced after serial dilatation. A 26 Fr nephroscope is then inserted through the working sheath, and the stone is fragmented and removed. Finally, a nephrostomy drain tube is kept at the puncture site. The outcome was accessed in terms of stone clearance rate after PCNL on the 2nd postoperative day using the radiological modality of CT-KUB. Results: Among the 115 patients here were 48(41.7%) categorized as GSS I, 26(22.6%) categorized as GSSII, 20(17.4%) categorized as GSS III, and 21(18.3%) categorized as GSS IV. The overall stone clearance observed was 64.3%, individual stone clearance was GSS I=91.66%, GSS II=53.84%, GSS III=50%, and GSS IV=28.57%. Stone clearance among the different GSS categories was significantly different (p<0.01). Conclusion: The Guy's Stone Score, based on CT scan findings, is a significant system in predicting successful stone-free rates. It is a convenient, quick, and efficient tool for pre-operative assessment, and it can be incorporated as a mandatory protocol before planning PCNL.